Pengembangan kompetensi pendidik dalam penyusunan lesson plan dalam pembelajaran daring di Lembaga Pendidikan Al-Ma’arif Kuningan - Riza Zahrah; Fajar Nugraha; Hatma Heris Mahendra; Dudung Suryana (Abdimas Siliwangi, 2023)
Under a shade foundation tumenggung argawijaya stand about three educational institutions as paud al-ma’arif, TPA/TKAal-ma’arif and DTA al-ma’arif. Educational institutions al-ma’arif have problem of the human resources and motivation , innovation and creativity at the low who implicates the educational and teaching that goes. Improvement of human resources in improving innovation in the third year, creativity in preparation for the learning in the covid 19. Activities to increase innovation and creativity in the third year of human resources development activities done the lesson plan in the pandemic covid 19. The outer covering: creativity to be achieved, innovation educator in the learning process for students improve learning outcomes in the preparation of the creation of habitual learning in the pandemic covid 19. A method of execution used in the general pkm covers the transfer of the model of learning which can be used and assistance sustainable of the implementation gradually on the preparation of as well as the learned plan.